About Some Families of Nonexpansive Mappings with respect to Renorming. (28th November 2016) - Acosta-Portilla, Juan Rafael; Hernández-Linares, Carlos Alberto; Pérez-García, Víctor
Abstract : We characterize the family of nonexpansive mappings which are invariant under renormings and we also compare the families of nonexpansive mappings under two equivalent norms.